When Empathy Works: Towards Finding Effective Ways of Sustaining Empathy Flow - Gill, Lesley; Schaddelee, Marjolein; Ramsey, Phil L; Turner, Sam; Naylor, Tom (Department of Management, Faculty of Economics and Business, Brawijaya University, 2018)
The need for developing empathy skills in the workplace continues to challenge organisations today. Findings from earlier research highlighted the need for developing these empathy skills. Interviews were undertaken in early 2017 with a mix of empathy trainers and managers of organisations where empathy is signalled as a key skill. The purpose of the inquiry was to explore their perspectives of empathy so as to discover emerging themes that increase our understanding of empathy in the workplace, elucidate optimal ways for developing oneâ€™s empathy and for reducing or mitigating empathy burnout. Challenges that emerged from the findings were: maintaining empathy across professional and personal environments; generally participants found they had energy for one of other, not both; caring too much; having time to empathise; managing expectations; professional boundaries; empathy equality i.e. to victim and offender; communicating empathy, and desensitisation. This paper explores these challenges. Four themes emerged from the findings: interpretations of empathy, context; including theory of mind, empathy burnout, and strategies for developing empathy. These themes informed the development of a Flow Model of Empathy.Â